The Federal Parliament of Nepal: An Examination of Inclusive Representation, 2022 (Samsad Journal संसद जर्नल, 2024)
Nepal is a country of varied and fair depiction of people from all backgrounds, makes the country multicultural, multilingual, multiethnic, multireligious, and diverse in terms of geography. Inequality in Nepal is still rife due to caste, ethnicity, religion, language, class, gender, and region, despite previous attempts at democratization and addressing issues of exclusion. The study is based on pragmatist philosophy. Multicultural and representative theories are appropriate for this study. Consequently, the study is ideally viewed as having significantly aided the federal parliament in the process of formulating policy. The representation percentage shows with the exception of Khas Arya, is significantly less than the quota assigned to these groups, despite the fact that the PR system has yielded positive results. Legislation pertaining to inclusive representation by the relevant authority needs to be changed in order to guarantee that the inclusive standards and values are fairly promoted and upheld.